PENGARUH SENAM HAMIL TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III - Mardalena Mardalena (Masker Medika, 2023)
ABSTRACT Background: Psychological changes that often occur in pregnant women are anxiety, The anxiety experienced by pregnant women is caused by an increase in the hormone progesterone. Pregnancy anxiety is proven to be reduced through physical exercise, one of which is by pregnancy exercises. Pregnancy exercise is one way to reduce anxiety in pregnant women. The purpose of this study was to determine the effect of pregnancy exercise on anxiety levels in timester 3 pregnant women at PMB Meli Rosita Palembang. Method: this research design was carried out with a quasi-experimental method using a two-group pre and posttest design, the research subjects were III trimester prenatal mothers, using purpose sampling techniques. Research instrument with HARS questionnaire. This study used univariate and bivariate data analysis to determine the effect of pregnancy exercise on anxiety levels in III trimester pregnant women. The pretest results found moderate anxiety of 61.3% and severe anxiety of 35.5% after the intervention, the results of the posttest scores obtained mild anxiety (38.7%), and severe anxiety (3.2%). The results of the analysis test found a value of ρ = 0.000 and a value of ρ smaller than α (5%) or 0.05 which means there is a significant influence of pregnancy exercise on anxiety levels in III trimester pregnant women. Conclusion: There was a decrease in anxiety levels before intervention and after intervention, so there was an effect of pregnancy exercise on the anxiety level of prenatal pregnant women in the third trimester. Keywords: Anxiety leve, Pregnant gymnastic, Third trimester